Unraveling Predominantly Inattentive ADHD (ADHD-PI): Insights from Proteomic Analysis of the Striatum of Thyroid Hormone-Responsive Protein (THRSP)–Overexpressing Mice - Raly James Perez Custodio; Leandro Val Sayson; Ara Cho; Hyeryeon Jung; Darlene Mae Ortiz; Hyun Jun Lee; Emad Alyan; Edmund Wascher; Stephan Getzmann; Mikyung Kim; Kyeong‑Man Kim; Eugene C. Yi; et al. (Molecular Neurobiology, 2025)
Attention-deficit/hyperactivity disorder, or ADHD, is a neurodevelopmental disorder with poorly understood molecular mechanisms. Recent studies have proposed that gene expression involved in regulating synaptic transmission in the striatum may play a role in ADHD pathogenesis. To explore the molecular basis of ADHD, we utilized proteomic analysis using whole striatal tissues from early adult thyroid hormone-responsive protein-overexpressing (THRSP-OE) mice, which displayed defining characteristics of predominantly inattentive ADHD (ADHD-PI). We focused on the striatal brain region due to its critical role in the regulation of attention, motivation, and reward processing. Moreover, the striatum modulates dopaminergic pathways that are known to be impaired in ADHD. Our analysis revealed an innate overexpression of Snap25 protein in THRSP-OE mice, indicating possible alterations in the SNARE protein complex and potential neurotransmitter dysregulation. Furthermore, a binding affinity study showed reduced dopamine D1 receptor binding concentrations and pronounced low dopamine levels in THRSP-OE mice. Repeated seven-day injections of methylphenidate improved the low dopamine levels, reducing the EEG theta/beta ratio in this animal model. These findings suggest new markers specific to the ADHD-PI presentation and further support the role of Snap25 dysregulation and possible SNARE protein complex alterations in ADHD-PI.

The impact of physical fitness, social life, and cognitive functions on work ability in middle-aged and older adults - Jennifer A. Rieker; Patrick D. Gajewski; José Manuel Reales; Soledad Ballesteros; Klaus Golka; Jan G. Hengstler; Edmund Wascher; Stephan Getzmann (International Archives of Occupational and Environmental Health, 2023)
Objective Demographic changes encompass societies to maintain the work ability (WA) of aging workforces. The present study explored the relationship between modifiable lifestyle factors, cognitive functions, and their influence on WA, using a multi-group structural equation approach. Method Cross-sectional data from 247 middle-aged and 236 older employees from the Dortmund Vital Study were included in this analysis. We proposed a model with three exogenous variables (Physical Fitness, Cognitive Functions, and Social Life), and with WA as the endogenous variable. WA was measured with the Work Ability Index (WAI), which considers job demands and individual physical and mental resources. Multi-group analyses were based on the principles of invariance testing and conducted using robust estimation methods. Results Results revealed that Social Life outside work had significant positive effects on WA in both, middle-aged and older adults. Physical Fitness had a significant effect on WA only in middle-aged adult, and Cognitive Functions had no significant influence on WA in either group. In older adults, Physical Fitness correlated with Cognitive Functions, whereas in middle-aged adults, Cognitive Functions marginally correlated with Social Life. Conclusions Our results underline the importance of an active social life outside the workplace for WA, regardless of the employees’ age. The influence of Physical Fitness on WA changes with increasing age, indicating the necessity to have a differentiated view of age effects and interacting influencing factors. Our research contributes to the knowledge of how WA could be most effectively promoted in different age groups. Clinicaltrials.gov NCT05155397; https://clinicaltrials.gov/ct2/show/NCT05155397 .

Frontal and parietal EEG alpha asymmetry: a large-scale investigation of short-term reliability on distinct EEG systems - Dorothea Metzen; Erhan Genç; Stephan Getzmann; Mauro F. Larra; Edmund Wascher; Sebastian Ocklenburg (Brain Structure and Function, 2022)
EEG resting-state alpha asymmetry is one of the most widely investigated forms of functional hemispheric asymmetries in both basic and clinical neuroscience. However, studies yield inconsistent results. One crucial prerequisite to obtain reproducible results is the reliability of the index of interest. There is a body of research suggesting a moderate-to-good reliability of EEG resting-state alpha asymmetry, but unfortunately sample sizes in these studies are typically small. This study presents the first large-scale short-term reliability study of frontal and parietal EEG resting-state alpha asymmetry. We used the Dortmund Vital Study data set containing 370 participants. In each participant, EEG resting state was recorded eight times, twice with their eyes opened, twice with their eyes-closed, each on two different EEG systems. We found good reliability of EEG alpha power and alpha asymmetry on both systems for electrode pairs. We also found that alpha power asymmetry reliability is higher in the eyes-closed condition than in the eyes-open condition. The frontomedial electrode pair showed weaker reliability than the frontolateral and parietal electrode pairs. Interestingly, we found no population-level alpha asymmetry in frontal electrodes, one of the most investigated electrode sites in alpha asymmetry research. In conclusion, our results suggest that while EEG alpha asymmetry is an overall reliable measure, frontal alpha asymmetry should be assessed using multiple electrode pairs.

The ultra-slow NAT2*6A haplotype is associated with reduced higher cognitive functions in an elderly study group - Silvia Selinski; Stephan Getzmann; Patrick D. Gajewski; Meinolf Blaszkewicz; Jan G. Hengstler; Michael Falkenstein; Klaus Golka (Archives of Toxicology, 2015)

Constancy of target velocity as a critical factor in the emergence of auditory and visual representational momentum - Stephan Getzmann; Jörg Lewald (Experimental Brain Research, 2009)

Saltation in pitch perception - Stephan Getzmann (Experimental Brain Research, 2007)

Representational momentum in spatial hearing does not depend on eye movements - Stephan Getzmann (Experimental Brain Research, 2005)